Evaluation of positional accuracy of digital topographic maps at scale 1:25 000 (DTM25) on the basis of STANAG 2215 standard - Drobnjak, Siniša M.; Božić, Branko S. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The paper describes the results of the positional accuracy assessment of digital topographic maps at scale 1: 25 000 produced by the Serbian Military Geographic Institute (MGI). The test for the horizontal and vertical accuracy compliance of map sheets is done by comparing the planimetric and height coordinates of the ground points to the coordinates of the same points as determined by a check survey of higher accuracy. In this research STANAG 2215 standard was used and the methodology of its use is discussed in detail. The results of positional accuracy assessment for the digital topographic maps at scale 1:25 000 produced by the Military Geographic Institute have confirmed the highest level of accuracy defined by STANAG 2215 standard.
Keywords: Positional accuracy; STANAG 2215 standard; Digital topographic maps; Military Geographical Institute